'Outspoken' Oral Hygienists Promote Oral Health Care Awareness at Public Events for (Pregnant) Women and Young Mothers - Yvonne A.B. Buunk-Werkhoven; Jolanda J.C. Gortzak; Judith J.E. Sjoerts; Annemarie Frederiks (The Korean Society of Dental Hygiene Science, 2021)
Background: The aim of these two (pre COVID-19 pandemic) public health studies in Amsterdam were to promote the profession of the oral hygienist and to increase oral health care awareness among (pregnant) women and young mothers, who were visitors of public consumer's exhibitions.Methods: Two cross-sectional studies were carried out. In 2018, during the first study, 1,765 visitors of the Household Fair completed a questionnaire. In 2020, during Study 2, 304 visitors of the Nine-Month Fair completed a semi-structured online questionnaire. At both fairs a team of 'outspoken' oral hygienists, i.e., members of the Foundation 'Goed Gebekt', provided the visitors with tailored advices about general health related to adults, mothers', and their children' oral health, using natural routine interviewing, that was based on their own professional daily practical experience. Results: In Study 1, just over half (53.5%) of a total of 1,742 visitors, (85.7% female) was younger than 45 years old. In Study 2, 210 visitors with a mean age of 30.7 years were included. Most women reported their self-perceived oral health as 'good' (mean=8.0, standard deviation=1.3; range 3∼10). Qualified (self) employed oral hygienists seem to be known among the visitors, but still only visited upon referral of the dentists. Up to the age of 18 reimbursements by the basic insurance is still unknown to the public. Conclusion: The Foundation 'Goed Gebekt' encourages other oral hygienists to make their own initiatives and experiences public and to share it. Public awareness is needed for oral health promotion and the development of optimally targeted interventions among (pregnant) women and young mothers by oral hygienists.